Generalized Vehicle Dynamics. - Williams, Daniel (Warrendale : SAE International, 2022)
An industry professional with more 30 years of experience in chassis control systems from concept to launch, Daniel Williams brings this experience and his unique approach to readers of Generalized Vehicle Dynamics.
13.3 The Three-Axle Model -- 13.4 Third Axle Steering -- 13.5 Trajectory Tracking -- 13.6 Summary -- References -- 14 Generalized Multiaxle Vehicle Dynamics -- 14.1 Introduction -- 14.2 General Model -- 14.3 An Arbitrarily Steered Axle -- 14.4  All Arbitrary Axles Steered Proportionally -- 14.5 The Multiaxle Vehicle with Roll -- 14.6 Summary -- References -- 15 Automated Vehicle Architecture from Vehicle Dynamics -- 15.1 Introduction -- 15.2  Properties of a Typical Three-Axle Commercial Vehicle -- 15.3 Control of Rear Axle -- 15.4  Rear Axle Control for Yaw Rate Equivalence -- 15.5 Vehicle Results -- 15.6 Proposed Three-Axle Vehicle -- 15.7 Summary -- References -- Afterword -- Index -- About the Author.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Motor vehicles--Dynamics.; Electronic books